Development And Validation Of The Extended Model Of Gifttedness And Talent (EMGT) Using Structural Equation Modeling - Al-Shabatat, Ahmad Mohammad Mahmoud (2010)
The concept of compounding of different abilities into a specific capability was demonstrated by Spearman (1905) and Mcgrew (1997) for the Cattell Horn Carroll Model using factor analysis but has remained unexplored since then and the effects of nurturing elements has also remained unresolved. This study investigated the Extended Model of Giftedness and Talent (EMGT) based on the compoundability hypothesis and the effects of nurturing elements such as environment and motivation on the development of giftedness and talent across the intellectual domain by developing new instruments and test items and employing statistical validation procedures using Structural Equation Modelling (SEM). The instrument consisted of culture-reduced test items that incorporated Cattell’s Culture-Fair Test (CCFT) items and tested for six standard subscales of intellectual aptitudes such as memory span, pattern recognition, sense of observation,